1997
DOI: 10.1111/j.1432-1033.1997.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diphtheria Mutant Toxin, Crm197, with a Haemophilus Influenzae Type‐b Polysaccharide‐Crm197 Conjugate by Optical Spectroscopy

Abstract: A Haemophilus influenzae type-b capsular polysaccharide-CRM197 protein conjugate vaccine was compared with unconjugated CRM197 and diphtheria toxin, its parent molecule. Using CD and fluorescence spectroscopy, it has been possible to observe differences in structure and stability to pH and temperature due to the G52-E mutation in CRM197 and the 'glycosylation' of CRM197 in the conjugate. begins unfolding at slightly lower temperatures (25-35 "C) than native material (> 35 "C). In the conjugate, tryptophan resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…These results are in agreement with previous studies performed on Hib and meningococcal group C CRM197 conjugates (Crane et al 1997;Ho et al 2001). Optical spectroscopy using circular dichroism (CD) and fluorescence spectroscopy were applied to CRM197 before and after conjugation.…”
Section: Conjugate Structuresupporting
confidence: 90%
“…These results are in agreement with previous studies performed on Hib and meningococcal group C CRM197 conjugates (Crane et al 1997;Ho et al 2001). Optical spectroscopy using circular dichroism (CD) and fluorescence spectroscopy were applied to CRM197 before and after conjugation.…”
Section: Conjugate Structuresupporting
confidence: 90%
“…polyribosyl ribitol phosphate). Previous observations with CD and fluorescence spectroscopic methods showed an increase in the mobility of the aromatic side chains in CRM 197 conjugated to Hib oligosaccharide when compared with that of the native CRM 197 [12]. These observations indicated that after conjugation, the CRM 197 was partially unfolded and adopted a slightly modified secondary structure and a more ‘open’ structure [17] in the conjugate molecule.…”
Section: Discussionmentioning
confidence: 91%
“…Inhibition studies were performed both with synthetic OS structures and fragments from PS degradation to determine optimal OSs for conjugation. The protein carrier used in the OS conjugates was CRM197, a nontoxic, immunologically cross-reacting mutant protein of diphtheria toxin (9,23) containing 39 lysine residues with a free ␣ amino terminus for attachment of multiple OS chains. For the development of effective synthetic glycoconjugate vaccines, the effects of different OSs and different conjugation chemistries, as well as the effect of the ratio of protein to carbohydrate (OS loading), on the immunogenicity of the glycoconjugates were studied.…”
mentioning
confidence: 99%